Dynamical Relations in the Self-Pattern - Gallagher, Shaun; Daly, Anya (Frontiers in Psychology, 2018)
The notion of a self-pattern, as developed in the pattern theory of self (Gallagher 2013), which holds that the self is best explained in terms of the kind of reality that pertains to a dynamical pattern, acknowledges the importance of neural dynamics, but also expands the account of self to extra-neural (embodied and enactive) dynamics. The pattern theory of self, however, has been criticized for failing to explicate the dynamical relations among elements of the self-pattern (e.g., Beni 2016; de Haan et al. 2017; Kyselo 2014); as such, it seems to be nothing more than a mere list of elements. We’ll argue that the dynamics of a self-pattern are reflected in three significant and interrelated ways that allow for investigation. First, a self-pattern is reflectively reiterated in its narrative component. Second, studies of psychiatric or neurological disorders can help us understand the precise nature of the dynamical relations in a self-pattern, and how they can fail. Third, referencing predictive processing accounts, neuroscience can also help to explicate the dynamical relations that constitute the self-pattern.